Producción de contenidos culturales: Laguna Sessions - sesiones musicales con bandas de la escena limeña - Vásquez Ochoa, Jagoda Dagmara (2020)
This report is about the realization of the audiovisual project: Laguna Sessions, which consisted of recording music sessions for independent national bands. Each one was recorded in La Laguna de la Molina and featured two videos: a song by day; and the second, at night, always trying to transmit simplicity, freshness and fun throughout the two takes, such as through the direct sound captured live, in such a way that the band looks real, as it is in live performance. The purpose of the project was to show the emerging Peruvian music projects, creating content and offering new resources for the diffusion of their songs.